A Necessary Revolution: For the Effective Presence of the Theater of the Oppressed in the Theater’s Bachelor’s Degrees (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article maps the presence or absence of the Theater of the Oppressed in the Bachelor’s Degrees in Theater of Public Universities in the Southeast of Brazil, making use of the analysis of Pedagogical Political Projects and the curriculum summary of such institutions, in addition to semi-structured interviews with artist-teachers, researchers, scholars of the subject. From this study, it shows the impacts and contributions that the method created by Augusto Boal can offer to the training of theater teachers, as well as to basic education. Finally, it proposes the curricular design of a discipline centrally dedicated to the Theater of the Oppressed as a possible and necessary revolution.
Keywords: Theater of the Oppressed; Degree in Theater; Teacher Training; Augusto Boal